Digital twin-based optimization and demo-scale validation of absorption columns using sodium hydroxide/water mixtures for the purification of biogas streams subject to impurity fluctuations - Pallavicini, Jacopo; Fedeli, Matteo; Scolieri, Giacomo Domenico; Tagliaferri, Francesca; Parolin, Jacopo; Sironi, Selena; Manenti, Flavio (Renewable energy, 2023)
This paper aims to validate a demo scale plant scrubber technology through experimental campaign and development of a digital twin. Thus, it is useful to evaluate the H2S absorption process in a biogas production plant for analysis and optimization purposes. The absorber unit removes H2S through the chemical absorption via sodium hydroxide (NaOH) as wet agent (30% w/w). The column treats 300 Nm3/h of biogas, whose inlet H2S concentration ranges from 1000 to 3000 ppm. Field measurements are conducted to investigate the H2S removal efficiency. An experimental dataset is collected, processed and used as input on Aspen PLUS suite to develop the digital twin. This model is helpful to generate a large dataset and simulate operating conditions different from the demo-scale plant. The process simulation is then exploited to perform a sensitivity analysis to figure out main variables influencing the H2S removal efficiency. Operating conditions such as H2S concentration, soda concentration and flowrate, temperature, and freshwater flowrate are perturbed in the sensitivity analysis. NaOH flowrate and its concentration are the variables with the biggest impact on the process. In detail, the highest efficiency performance was obtained using 50% NaOH solution with a flowrate higher than 8 kg/h. [Display omitted] •Experimental campaigns are performed to validate the biogas scrubbing technology.•A digital twin is computed to study and optimize the demo-scale plant.•The discrepancy between the on-field unit and its digital twin is always lower than 6%.•The digital twin allows generating a larger dataset to assess sensitivity analysis.•NaOH flowrate is the most influencing parameter for biogas scrubbing removal efficiency.